2012
DOI: 10.1530/eje-12-0512
|View full text |Cite
|
Sign up to set email alerts
|

Serum myostatin levels are negatively associated with abdominal aortic calcification in older men: the STRAMBO study

Abstract: Objective: To assess the association between abdominal aortic calcification (AAC) and serum levels of myostatin, a negative regulator of skeletal muscle mass, which has been implicated in the development of atherosclerotic lesions in mice. Design and patients: We assessed AAC semiquantitatively from the lateral spine scans obtained using dual energy X-ray absorptiometry in 1071 men aged 20-87 years. Serum myostatin levels were measured by an immunoassay that detects all myostatin forms. Results: Total myostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
3
4
0
Order By: Relevance
“…Indeed, in contrast to early observations highlighting a link between elevated levels of Mstn and low muscularity situations, [41][42][43] recent studies showed a decrease of circulating Myostatin in conditions characterized by reduced skeletal muscle mass such as ageing, but without correlation between Myostatin levels and muscle mass. [44][45][46] In agreement with our results, Breitbart et al observed in cancer patients with body weight loss a decrease of circulating Myostatin propeptide levels, reflecting a decrease of Myostatin production. 47 The lack of consistency between these studies might be explained by the use of various immunoassays detecting different forms of Myostatin and a possible cross-reactivity with other TGFβ members.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, in contrast to early observations highlighting a link between elevated levels of Mstn and low muscularity situations, [41][42][43] recent studies showed a decrease of circulating Myostatin in conditions characterized by reduced skeletal muscle mass such as ageing, but without correlation between Myostatin levels and muscle mass. [44][45][46] In agreement with our results, Breitbart et al observed in cancer patients with body weight loss a decrease of circulating Myostatin propeptide levels, reflecting a decrease of Myostatin production. 47 The lack of consistency between these studies might be explained by the use of various immunoassays detecting different forms of Myostatin and a possible cross-reactivity with other TGFβ members.…”
Section: Discussionsupporting
confidence: 93%
“…Although Myostatin is doubtless an inhibitor of skeletal muscle mass development, its role in muscle atrophy remains unclear. Indeed, in contrast to early observations highlighting a link between elevated levels of Mstn and low muscularity situations,41, 42, 43 recent studies showed a decrease of circulating Myostatin in conditions characterized by reduced skeletal muscle mass such as ageing, but without correlation between Myostatin levels and muscle mass 44, 45, 46. In agreement with our results, Breitbart et al .…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were reported in the STRAMBO study, which investigated in a large cohort of healthy men the association between serum levels of Mstn and abdominal aortic calcifications evaluated through spine dual-energy X-ray absorptiometry. In this case, the authors confirmed that, at least in older men, total Mstn serum levels were inversely correlated with vascular calcifications [98].…”
Section: Myostatin and Vascular Calcificationsupporting
confidence: 69%
“…Patients with high myostatin levels had lower AAC scores than did those with low myostatin levels, indicating potentially favorable effects on VC in dialysis patients. Szulc et al [10] reported previously in the Structure of the Aging Men’s Bones (STRAMBO) study that older males with AAC have lower myostatin levels than those without AAC. Generally, the expression of myostatin and the severity of vascular damage show a positive correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the abdominal aortic calcification (AAC) score on plain radiography has a very good correlation with the identification of coronary artery calcification and low bone mass, which are risk factors for mortality [8,9]. A previous human study reported that serum myostatin levels were negatively associated with AAC in older males [10]. However, no research has been conducted on the relationship between myostatin levels and AAC in dialysis patients at this time, to our knowledge.…”
Section: Introductionmentioning
confidence: 99%